Steel silo structures on discrete supports - Li, Hongyu (University of Edinburgh; College of Science & Engineering; School of Engineering & Electronics, 1994)
The objective of this thesis is to broaden current knowledge of the strength and buckling/collapse of shells, with special reference to steel silo structures on discrete supports, and thus to provide design guidance of practical value for future silo design and construction and to develop new research aspects for further investigation. A linear elastic solution of the cylindrical shell bending equations is presented for local loadings, with special attention to local longitudinal distributed loadings. Algebraic expressions for the displacements and stresses induced by a rectangular patch of longitudinal load on a simply supported cylindrical shell are derived using double Fourier series. The solution of this problem is general, and therefore can be applied to cylindrical shells under local I loadings in any direction and with different boundary conditions. Linear elastic analyses of discretely supported perfect cylinders under axial compression are presented using the finite element method. The pre-buckling meridional membrane stress distribution above the support centreline is examined in detail, and is followed by investigations of the linear bifurcation behaviour of the cylinders. The effects on the stress distribution and the buckling strength of different loading patterns and different geometric configurations are extensively examined. Geometrically nonlinear elastic buckling analyses are also performed using large deflection theory. Both perfect and imperfect cylinders are studied with various geometric configurations and under different loading conditions. The nonlinear elastic buckling behaviour, the buckling strength and the buckling configuration are thoroughly investigated for discretely supported cylinders. Further studies extend the work into the plastic range. Discretely supported cylinders obeying the von Mises yield criterion are analysed. Limit analyses of perfect cylinders are first conducted using small deflection theory. Geometrically nonlinear elastic-plastic collapse analyses of both perfect and imperfect cylinders are performed next. Studies of different loading conditions and parametric studies of varying geometries and material strengths are presented in both types of analysis. The nonlinear elastic-plastic behaviour of discretely supported cylinders is thus explored. A complete silo which consists of a cylindrical shell, a conical roof hopper and a conical discharge hopper is briefly examined, with the aim of exploring the applicability of the established cylinder model in the elastic buckling analysis of silo structures. Finally, the conclusions drawn from this research are summarised and recommendations are also made for further research on locally supported shells.
Analysis of steel silo structures on discrete supports